A DESCRIPTIVE STUDY ON ENGLISH SPEAKING TEACHING-LEARNING PROCESS AT THE EIGHT YEAR STUDENTS OF SMP N 1 BOYOLALI IN 2010/2011 ACADEMIC YEAR - WIDAYAT , ZENING LILIH AVRILIANI (2011)
The aims of the study are to describe the technique applied of teaching learning of speaking process, to identify the problem faced by the teacher and the students, and to know the problem solving used by the teacher. The type of this research is descriptive qualitative which does not use any calculation or enumerating. The method of collecting data is descriptive method by doing observation, checking document and employing interview with the teacher and the students. The data are taken from all elements of the English speaking teaching-learning process committed by the teacher and the students and other sources such as document, speaking materials, syllabus, etc. The result of the research shows that the English teacher of the eight year students in SMP N 1 Boyolali applies four methods in teaching speaking such as GTM, DM, CLL, and CLT by combining them with various techniques such as Role-play, games, conversation practice, and repetition and translation. The problems faced by the teacher are classroom management, limited time, and different competencis of the students. The problems faced by the students are limited vocabulary, pronunciation, grammar, and nervousness. Then, the problem solving applied by the teacher are giving advices and motivation about the importance of their activity in speaking class, creating good relation between the teacher and the students, giving more exercises about grammar to the students, and accepting the consultation from the students about the difficult material out of class.